2016
DOI: 10.1016/j.buildenv.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of triphenylphosphine oxide and other organophosphorus compounds in indoor air and settled dust of an institute building

Abstract: Please cite this article as: Faiz Y, Zhao W, Feng J, Sun C, He H, Zhu J, Occurrence of triphenylphosphine oxide and other organophosphorus compounds in indoor air and settled dust of an institute building, Building and Environment (2016), AbstractIndoor environments contain a wide range of synthetic products that emit a variety of semi-volatile organic compounds (SVOCs). Among these SVOCs, organophosphorus compounds (OPs) are ubiquitous in indoor environments with relatively high concentrations.This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This similarity likely reflects analogous sources of OPFRs in these indoor microenvironments. Unlike these countries, in China, TCEP and TCIPP were the dominant compounds in private homes and offices (Figure A,B), while TCEP was dominant in daycare centers (Figure C) . Such differences can be explained by the fact that there is no legislative restriction on the production and use of TCEP in China to date, while TCEP is restricted under the 2006 REACH legislation in Europe and equivalent legislation in the USA .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This similarity likely reflects analogous sources of OPFRs in these indoor microenvironments. Unlike these countries, in China, TCEP and TCIPP were the dominant compounds in private homes and offices (Figure A,B), while TCEP was dominant in daycare centers (Figure C) . Such differences can be explained by the fact that there is no legislative restriction on the production and use of TCEP in China to date, while TCEP is restricted under the 2006 REACH legislation in Europe and equivalent legislation in the USA .…”
Section: Resultsmentioning
confidence: 98%
“…Linked to the ubiquitous presence of OPFRs in indoor environments and their potential for adverse health effects, there is increasing concern about human exposure to OPFRs. Concentrations and exposure assessments of OPFRs in indoor dust have been reported in various countries and regions, including China, Japan, Sweden, the USA, Canada, Denmark, Egypt, Belgium, Kuwait, Pakistan, Romania, the Netherlands, and the UK . Most of these studies focused on private homes and offices, rather than on other microenvironments, like building material markets and floor/carpet stores, even though polyurethane foam (PUF) insulation materials and plasticizers have been implicated as the major sources of OPFRs in indoor air at such locations .…”
Section: Introductionmentioning
confidence: 99%
“…Background contamination is an important issue to take into account when working with PFRs since they are widely used in lab material and equipment, and their presence is known in indoor air and dust . Different strategies have been developed to minimize blank contamination during the sample preparation: minimizing surface contact during sample handling by reducing clean‐up, performing extraction and evaporation steps, working in a cleanroom, precleaning all glassware with a polar and nonpolar solvent , and rinsing the walls of this glassware with an organic solvent .…”
Section: Methodsmentioning
confidence: 99%
“…A few recent studies have reported carcinogenic and neurotoxic potentials of chlorinated OPEs and tris­(2-butoxyethyl) phosphate (TBOEP), , and exposure to OPEs has been linked to reproductive effects in humans . Further, OPEs have been found to be ubiquitous in various environmental matrices, such as outdoor air, indoor air, , indoor dust, water, sediment, , soil, and biota. …”
Section: Introductionmentioning
confidence: 99%